Peran Komunitas Moslem Youth Creative Terhadap Penguatan Aqidah Pemuda Di Desa Batang Kuis Pekan - Uly Halimah (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2021)
Now humans are creatures filled with various visible temptations. Thus, humans must have something that guides their lives, namely aqidah. The application of aqidah in today's youth is very important as it is expected to be a balance and control for the behavior of mankind, now it seems that it has not been able to play a role as desired. For this reason, the role of the Moslem Youth Creative Community is very much needed in instilling aqidah values in today's youth so that they will be able to become good and quality national shoots.Departing from these problems, the author has the initiative to conduct research on the role of the Moslem Youth Creative Community towards strengthening the aqidah of youth in Batang Kuis Pekan Village. The problem of this research is how the role of the Moslem Youth Creative Community in strengthening the youth aqidah includes instilling the values of aqidah, worship and morals. This study uses a field research method that uses observation data collection methods, interviews involving the Moslem Youth Creative Community, the community, preachers and several youth members of the village mosque, and documentation. While the method of data analysis using descriptive methods, and phenomenological methods.The descriptive method aims to describe the situation, and is used to determine the interests and aspirations of the Moslem Youth Creative community towards youth strengthening in Batang Kuis Pekan Village. While the phenomenological method is an approach that studies the symptoms of the Moslem Youth Creative community found from experience and reality in the field.